{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Homework 7

Homework 7 - Garcia Ilse Homework 7 Due Oct 9 2007 3:00 am...

This preview shows pages 1–3. Sign up to view the full content.

Garcia, Ilse – Homework 7 – Due: Oct 9 2007, 3:00 am – Inst: Fonken 1 This print-out should have 18 questions. Multiple-choice questions may continue on the next column or page – find all choices before answering. The due time is Central time. 001 (part 1 of 1) 10 points Find the derivative of f when f ( x ) = 5 x cos 4 x . 1. f 0 ( x ) = 20 cos 4 x + 4 x sin 4 x 2. f 0 ( x ) = 5 cos 5 x - 5 x sin 4 x 3. f 0 ( x ) = 5 cos 4 x - 20 x sin 4 x correct 4. f 0 ( x ) = 5 cos 4 x + 20 x sin 5 x 5. f 0 ( x ) = 20 cos 4 x - 5 x sin 4 x Explanation: Using the formulas for the derivatives of sine and cosine together with the Chain Rule we see that f 0 ( x ) = (5 x ) 0 cos 4 x + 5 x (cos 4 x ) 0 = 5 cos 4 x - 20 x sin 4 x . keywords: derivative, trig function, chain rule 002 (part 1 of 1) 10 points Find the value of f 0 (0) when f ( x ) = (1 - 4 x ) - 2 . Correct answer: 8 . Explanation: Using the chain rule and the fact that ( x α ) 0 = α x α - 1 , we obtain f 0 ( x ) = 8 (1 - 4 x ) 3 . At x = 0, therefore, f 0 (0) = 8 . keywords: derivative, chain rule 003 (part 1 of 1) 10 points Find f 0 ( x ) when f ( x ) = p x 2 - 6 x . 1. f 0 ( x ) = 2( x - 3) x 2 - 6 x 2. f 0 ( x ) = x - 3 x 2 - 6 x correct 3. f 0 ( x ) = 1 2 ( x - 3) p x 2 - 6 x 4. f 0 ( x ) = 2( x - 3) p x 2 - 6 x 5. f 0 ( x ) = x - 3 2 x 2 - 6 x 6. f 0 ( x ) = ( x - 3) p x 2 - 6 x Explanation: By the Chain Rule, f 0 ( x ) = 1 2 x 2 - 6 x (2 x - 6) . Consequently, f 0 ( x ) = x - 3 x 2 - 6 x . keywords: derivative, square root, chain rule 004 (part 1 of 1) 10 points

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Garcia, Ilse – Homework 7 – Due: Oct 9 2007, 3:00 am – Inst: Fonken 2 Find f 0 ( x ) when f ( x ) = 1 6 x - x 2 . 1. f 0 ( x ) = x - 3 ( x 2 - 6 x ) 3 / 2 2. f 0 ( x ) = x - 3 (6 x - x 2 ) 1 / 2 3. f 0 ( x ) = 3 - x ( x 2 - 6 x ) 1 / 2 4. f 0 ( x ) = 3 - x (6 x - x 2 ) 3 / 2 5. f 0 ( x ) = 3 - x ( x 2 - 6 x ) 3 / 2 6. f 0 ( x ) = x - 3 (6 x - x 2 ) 3 / 2 correct Explanation: By the Chain Rule, f 0 ( x ) = - 1 2(6 x - x 2 ) 3 / 2 (6 - 2 x ) . Consequently, f 0 ( x ) = x - 3 (6 x - x 2 ) 3 / 2 . keywords: derivative, square root, chain rule 005 (part 1 of 1) 10 points Determine f 0 ( x ) when f ( x ) = 1 + 2 x 1 + x 2 . 1. f 0 ( x ) = 2 + x (1 + x 2 ) 3 / 2 2. f 0 ( x ) = x + 2 (1 + x 2 ) 1 / 2 3. f 0 ( x ) = x - 2 (1 + x 2 ) 1 / 2 4. f 0 ( x ) = 2 - x (1 + x 2 ) 1 / 2 5. f 0 ( x ) = x - 2 (1 + x 2 ) 3 / 2 6. f 0 ( x ) = 2 - x (1 + x 2 ) 3 / 2 correct Explanation: By the Product and Chain Rules, f 0 ( x ) = 2 (1 + x 2 ) 1 / 2 - 2 x (1 + 2 x ) 2(1 + x 2 ) 3 / 2 = 2(1 + x 2 ) - x (1 + 2 x ) (1 + x 2 ) 3 / 2 . Consequently, f 0 ( x ) = 2 - x (1 + x 2 ) 3 / 2 . (Note: the Quotient Rule could have been used, but it’s simpler to use the Product Rule.) keywords: derivative, quotient rule, chain rule 006 (part 1 of 1) 10 points Find f 0 ( x ) when f ( x ) = 2 cos 2 x + 3 cos 2 x .
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

What students are saying

• As a current student on this bumpy collegiate pathway, I stumbled upon Course Hero, where I can find study resources for nearly all my courses, get online help from tutors 24/7, and even share my old projects, papers, and lecture notes with other students.

Kiran Temple University Fox School of Business ‘17, Course Hero Intern

• I cannot even describe how much Course Hero helped me this summer. It’s truly become something I can always rely on and help me. In the end, I was not only able to survive summer classes, but I was able to thrive thanks to Course Hero.

Dana University of Pennsylvania ‘17, Course Hero Intern

• The ability to access any university’s resources through Course Hero proved invaluable in my case. I was behind on Tulane coursework and actually used UCLA’s materials to help me move forward and get everything together on time.

Jill Tulane University ‘16, Course Hero Intern